EDITORIAL - Palhano, Angelo; Matos Lima Melo, Felipe; Carreiro Cruz, Francisco Edson; Leiros Sarmento da Silva, Iasmin; Oliveira Chaia, Jade; da Rocha Pacheco, Lauro Vinícius; Rodrigues Rocha, Maria Clara; Alves Teixeira, Michelly; Rossinetti Rufinoni, Priscila (PÓLEMOS – Revista de Estudantes de Filosofia da Universidade de Brasília, 2017)
Editorial do número 06, volume 11, ano 2017.